2019
DOI: 10.1111/avj.12840
|View full text |Cite
|
Sign up to set email alerts
|

Predation by carpet pythons (Morelia spilota) is an important cause of mortality in a free‐living koala (Phascolarctos cinereus) population in South East Queensland

Abstract: Koalas (Phascolarctos cinereus) are experiencing significant declines across the northern part of their range. However, unbiased, population-level estimates of mortality are rarely reported, as it's difficult to quantify causes of mortality robustly in this cryptic species. We aimed to determine the relative importance of carpet python (Morelia spilota) predation in a free-living koala population and describe the characteristic pathological findings during necropsy. In total, 503 koalas were captured, underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Although individual animals are known to occasionally consume prey that tax their anatomical limit for prey size, the frequency at which such events occur has remained an open question (Hertz et al, 1988;Jayne et al, 2022). Our results add to a growing body of evidence demonstrating that, in certain ecological contexts, snakes routinely attempt to consume prey items beyond the upper limit of their maximal gape (Robbins et al, 2019;Shine & Sun, 2003), with fatal effects on the prey and no documented impacts on the predator.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although individual animals are known to occasionally consume prey that tax their anatomical limit for prey size, the frequency at which such events occur has remained an open question (Hertz et al, 1988;Jayne et al, 2022). Our results add to a growing body of evidence demonstrating that, in certain ecological contexts, snakes routinely attempt to consume prey items beyond the upper limit of their maximal gape (Robbins et al, 2019;Shine & Sun, 2003), with fatal effects on the prey and no documented impacts on the predator.…”
Section: Discussionmentioning
confidence: 64%
“…For example, Shedao Island Pit Vipers ( Gloydius shedaoensis ) are often observed capturing and attempting to feed on birds they are unable to swallow (Shine & Sun, 2003 ). A recent telemetry study on the survival of koala's ( Phascolarctos cinereus ) found that only slightly more than a third (38%) of the koalas killed by carpet pythons ( Morelia spilota ) were successfully ingested by the snakes (Robbins et al., 2019 ). There are also many anecdotal reports of snakes attempting to ingest oversized prey (Kornilev et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mapping (special modeling) (Mann & Benwell, 1996;Neldner et al, 1995) South Declining koala numbers (Beyer et al, 2018;Chen et al, 2020;Cristescu et al, 2019;Davey et al, 2022;Dexter et al, 2018;Dissanayake et al, 2021;Gonzalez-Astudillo et al, 2017;Gonzalez-Astudillo et al, 2019;Grogan et al, 2018;Jiang et al, 2021Jiang et al, , 2022Kerlin et al, 2022;Liz arraga et al, 2020;Mitchell, Soto-Berelov, Langford, & Jones, 2021;Pang et al, 2021;Robbins, Loader, et al, 2019;Rundle-Thiele et al, 2019;Schultz et al, 2020Schultz et al, , 2022Seddon & Schultz, 2020;Silver et al, 2022) Usage of ecological parameters and movement (Cristescu et al, 2019;Davey et al, 2022;Dissanayake et al, 2021;McAlpine et al, 2017;Santamaria et al, 2021;Schultz et al, 2022) Data collection method (Dissanayake et al, 2019, Dissanayake et al, 2021 Threats (Barbosa et al, 2017;Mitchell, Soto-Berelov, Langford, & Jones, 2021;Pang et al, 2021;Robbins, Loader, et al, 2019;Santamaria & Schlagloth, 2016;Schultz et al, 2020) Spatial modelling for koalas in South East Queensland koala habitat areas (KHA) v1.0. Technical report (Department of Environment and Science, 2020c) ...…”
Section: Resultsmentioning
confidence: 99%
“…possums, macropods). At present, the system does not incorporate features such as accelerometry to detect illness or death, as can be done with the Lx system (Robbins et al 2019b). Fossorial and strictly nocturnal species may be less suitable for this system, given the reliance of the tags on solar recharging, but the portable multi-platform interface and simple setup of this system are key advantages over current alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously used purpose-built store-on-board wildlife tracking collars (Ellis et al 2011;Robbins et al 2019aRobbins et al , 2019b and repurposed commercial GPS tags to attach to VHF tracking collars (Ellis et al 2016) to conduct such studies on koalas. Here we investigated the use of a low-power long-range (LoRa) system, to collect and transmit location data from koalas, in urban and rural settings.…”
Section: Introductionmentioning
confidence: 99%